A choice between RBD (refined, bleached, and deodorized) palm olein and palm methyl ester productions from carbon movement categorization. (August 2015) - Polprasert, Chongchin; Patthanaissaranukool, Withida; Englande, Andrew J.
Abstract: The purpose of this study was to evaluate the full-chain carbon cycle of oil palm to determine the CE (carbon equivalences), starting from plantation until production of end-user products including RBD (refined, bleached, and deodorized) Palm Olein as a cooking oil and PME (palm methyl ester) as biodiesel fuel. Based on the carbon categorization, the equivalent carbon emissions from RBD Palm Olein and PME productions were found to be 159 and 153 kg CE/ton product, respectively. The major emissions in the RBD Palm Olein production chain are attributed to the use of natural gas for energy spent in the industrial process and Poly Ethylene Terephthalate for product containers; whereas, those in the PME production are from methanol used in the transesterification. After identification of the carbon pathway, RBD Palm Olein exhibited a net emission of 116 kg CE/ha-y, but PME shows a net reduction of 2328 kg CE/ha-y. From energy balances and economic performances, PME is found to have higher net energy ratio, with 40% lower production cost per kg CE, than does RBD Palm Olein. Therefore, increasing the use of palm oil for biodiesel production rather than as use for cooking oil is justified as a useful tool for climate change mitigation. Highlights: Carbon cycle of palm oil was evaluated from plantation to end-user products. Carbon movement is classified based on fossil versus non-fossil related activities. Zero emission was simulated to find palm plantation to produce food and fuel. PME exhibits better net energy ratio and cost performances than does cooking oil.